Pelvic Binder Application: Classic Teaching Method vs Video-Based Learning - Andreia Balbino, Manuel Rosete, Henrique Alexandrino, Maria Koch, Eva Santos, José Lopes (Journal of the Portuguese Society of Anesthesiology, 2024)
Pelvic Binder Application: Classic Teaching Method vs Video-Based Learning